Neuroprotective Nanoparticles Targeting the Retina: A Polymeric Platform for Ocular Drug Delivery Applications - Patrizia Colucci; Martina Giannaccini; Matteo Baggiani; Breandán N. Kennedy; Luciana Dente; Vittoria Raffa; Chiara Gabellini (MDPI AG, 2023)
Neuroprotective drug delivery to the posterior segment of the eye represents a major challenge to counteract vision loss. This work focuses on the development of a polymer-based nanocarrier, specifically designed for targeting the posterior eye. Polyacrylamide nanoparticles (ANPs) were synthesised and characterised, and their high binding efficiency was exploited to gain both ocular targeting and neuroprotective capabilities, through conjugation with peanut agglutinin (ANP:PNA) and neurotrophin nerve growth factor (ANP:PNA:NGF). The neuroprotective activity of ANP:PNA:NGF was assessed in an oxidative stress-induced retinal degeneration model using the teleost zebrafish. Upon nanoformulation, NGF improved the visual function of zebrafish larvae after the intravitreal injection of hydrogen peroxide, accompanied by a reduction in the number of apoptotic cells in the retina. Additionally, ANP:PNA:NGF counteracted the impairment of visual behaviour in zebrafish larvae exposed to cigarette smoke extract (CSE). Collectively, these data suggest that our polymeric drug delivery system represents a promising strategy for implementing targeted treatment against retinal degeneration.